Identification of an intrinsic determinant critical for maspin subcellular localization and function. - Sijana H Dzinic; Alexander Kaplun; Xiaohua Li; Margarida Bernardo; Yonghong Meng; Ivory Dean; David Krass; Paul Stemmer; Namhee Shin; Fulvio Lonardo; Shijie Sheng (PLoS ONE)
Maspin, a multifaceted tumor suppressor, belongs to the serine protease inhibitor superfamily, but only inhibits serine protease-like enzymes such as histone deacetylase 1 (HDAC1). Maspin is specifically expressed in epithelial cells and it is differentially regulated during tumor progression. A new emerging consensus suggests that a shift in maspin subcellular localization from the nucleus to the cytoplasm stratifies with poor cancer prognosis. In the current study, we employed a rational mutagenesis approach and showed that maspin reactive center loop (RCL) and its neighboring sequence are critical for maspin stability. Further, when expressed in multiple tumor cell lines, single point mutation of Aspartate(346) (D(346)) to Glutamate (E(346)), maspin(D346E), was predominantly nuclear, whereas wild type maspin (maspin(WT)) was both cytoplasmic and nuclear. Evidence from cellular fractionation followed by immunological and proteomic protein identification, combined with the evidence from fluorescent imaging of endogenous proteins, fluorescent protein fusion constructs, as well as bimolecular fluorescence complementation (BiFC) showed that the increased nuclear enrichment of maspin(D346E) was, at least in part, due to its increased affinity to HDAC1. Maspin(D346E) was also more potent than maspin(WT) as an HDAC inhibitor. Taken together, our evidence demonstrates that D(346) is a critical cis-element in maspin sequence that determines the molecular context and subcellular localization of maspin. A mechanistic model derived from our evidence suggests a new window of opportunity for the development of maspin-based biologically competent HDAC inhibitors for cancer treatment.